Transformasi Sosial dan Politik dalam Perkembangan Islam di Era Nabi Muhammad SAW - Gerasela,; Yuliatin,; M Zalva Zakira,; Hudaidah,; Tyas Fernanda, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the social and political transformation during the era of the Prophet Muhammad SAWasthefoundation of Islamiccivilization. Before the arrival of Islam, Arab society lived under an unequal tribal system characterized by conflict and moral as well as spiritual decline. Using a qualitative approach through a literature review method, this research analyzes how the Prophet MuhammadSAWrestructured social and political systems based on the principles of monotheism, justice, and equality. The results show that Islam successfully reformed various aspects of life, including the abolition of slavery, the elevation of women’s status, and the establishment of an equitable economic system through zakat, the prohibition of usury, and the creation of Baitul Mal. Politically, the Medina Charter served as the foundation of a lawful and inclusive state that guaranteed religious freedom and upheld the principles of consultation and social justice. Thus, the transformation initiated by the Prophet was not only religious in nature but also laid the groundwork for the emergence of a humanistic, egalitarian, and civilized society